(untitled) (HEALTH CARE: JURNAL KESEHATAN, 2024)
The aim of this study was to determine the relationship between stroke history and self efficacy patient at the Jakarta Islamic Hospital. The method used is descriptive analytic with a cross-sectional approach. Multiple logistic regression analysis (multivariate) showed that patients with recurrent strokes are at risk of decreasing independence by 3.95 times compared to patients with first strokes.. Conclusion: there is a relationship between history of stroke and self efficacy after controlling for the patient’s age, gender and cognitive problems. Stroke patients with a history of first-time attacks can anticipate and prevent recurrent strokes from various factors that cause them in order to reduce the decline in its independence.